Tape-helix model of analysis for the dispersion and interaction impedance characteristics of a helix loaded with a double-negative metamaterial for potential application in vacuum electron devices. Issue 2 (22nd January 2019) - Varshney, Amit K.; Guha, Raktim; Biswas, Sushanta; Sarkar, Partha Pratim; Datta, Subrata K.; Basu, B. N.
ABSTRACT: The tape-helix model of analysis of a helix surrounded by a double-negative metamaterial tube in a metal envelope was developed adding a rigor to the earlier analysis that had used the simple sheath-helix model. The analyses using these two models were compared and validated against CST simulation. The structure supporting backward waves opens up the potential application of the structure in backward-wave vacuum electron device.